Rudy - Astin, Sean.; Beatty, Ned.; Dutton, Charles S.; Gooding, Jr., Cuba.; Harris, Ed. (Culver City, CA : Sony Pictures, 2006)
Rudy : The true story of a man told his entire life that he's not good enough, smart enough, or big enough, who never lets go of his dream to play football for Notre Dame.
Radio: Together with Head Coach Harold Jones and based on the real life story, Robert "Radio" Kennedy inspires a football team to become champions and a town to open their hearts.
Rudy (1993) -- Radio (2003).
Originally released as motion picture in 1993 and 2003.
Sean Astin ; Ned Beatty ; Charles S. Dutton ; Cuba Gooding Jr. ; Ed Harris.
MPAA rating: PG.
DVDs, Dolby digital 5.1.
Closed-captioned.
Keywords: University of Notre Dame -- Football -- Drama; Football -- Drama; People with mental disabilities -- Drama; Coaches (Athletics) -- Drama; School sports -- Drama; Sports films; Video recordings for the hearing impaired; Feature films